2014
DOI: 10.1080/14786419.2013.879306
|View full text |Cite
|
Sign up to set email alerts
|

A new guaianolide sesquiterpene lactone from Curcuma leucorrhiza Roxb.

Abstract: A naturally occurring guaianolide sesquiterpene lactone (1), along with 10 known compounds (2-11), was isolated from the chloroform extract of the dried rhizomes of Curcuma leucorrhiza Roxb. Their structures were elucidated on the basis of spectroscopic studies and X-ray crystallographic analysis. Compound 1 expressed antioxidant activity. The taxonomic status of C. leucorrhiza is briefly discussed based on the chemotaxonomic significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Phytochemical analysis of the rhizomes of C. leucorrhiza also revealed the presence of alkaloids, tannins, steroids, anthocyanins, terpenoids, triterpenoids, flavonoids, phenols, phlobatannins, and guaianolide sesquiterpene lactone. [66,72,73] Many steroids, tannins, alkaloids, and flavonoid compounds have also been reported from the rhizomes of C. pseudomontana and bioactive sesquiterpenes compounds such as germacrone, zederone, dehydrocurdione, curcumenol, zedoarondiol, and isocurcumenol along with β-pinene or other sesquiterpene lactones have been shown to be responsible for the antiandrogenic effect and uterine relaxant property of C. aeruginosa. [13,68,74] According to Mujumdar et al, [75] the ethyl alcohol extracts of C. amada rhizomes contain compounds with hydroxyl, ester, carbonyl, and olefin functional groups, which contributed to the anti-inflammatory activity of the extracts in acute and chronic administration in albino rats.…”
Section: Curcuma Zanthorrhizamentioning
confidence: 99%
“…Phytochemical analysis of the rhizomes of C. leucorrhiza also revealed the presence of alkaloids, tannins, steroids, anthocyanins, terpenoids, triterpenoids, flavonoids, phenols, phlobatannins, and guaianolide sesquiterpene lactone. [66,72,73] Many steroids, tannins, alkaloids, and flavonoid compounds have also been reported from the rhizomes of C. pseudomontana and bioactive sesquiterpenes compounds such as germacrone, zederone, dehydrocurdione, curcumenol, zedoarondiol, and isocurcumenol along with β-pinene or other sesquiterpene lactones have been shown to be responsible for the antiandrogenic effect and uterine relaxant property of C. aeruginosa. [13,68,74] According to Mujumdar et al, [75] the ethyl alcohol extracts of C. amada rhizomes contain compounds with hydroxyl, ester, carbonyl, and olefin functional groups, which contributed to the anti-inflammatory activity of the extracts in acute and chronic administration in albino rats.…”
Section: Curcuma Zanthorrhizamentioning
confidence: 99%
“…It was shown that the compound at a concentration of 250 μg/mL displayed an antioxidant activity equal to about 54.54 % of a reference solution of butylated hydroxyl toluene (125 μg/mL). The authors claimed that this compound might be a good candidate for studying cytotoxic or antiviral effects due to the presence of α‐methyl‐ɣ‐lactone, which also exists in our isolated compounds [51] …”
Section: Resultsmentioning
confidence: 99%
“…The authors claimed that this compound might be a good candidate for studying cytotoxic or antiviral effects due to the presence of α-methyl-�-lactone, which also exists in our isolated compounds. [51] Raola et al isolated two guaianolide-type sesquiterpene lactones, including (Z)-3α,4,5,6-tetrahydro-5α-isobutyl-2β-(meth- , from the natural hybrid mangrove Rhizophora annamalayana. They showed that compound B exhibited higher antioxidative activity in the DPPH assay than compound A.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…The genus Curcuma belongs to the Zingiberaceae family and is an important source of traditional medicines and is also used as a functional food, both the crude extracts and the essential oils of this genus are known for their biological activities (Rajashekhara and Sharma, 2010;Azam et al 2014). Essential oils of Curcuma species have been extensively studied, leading to the identification of several volatile compounds, of which terpenoids are dominant (Asem & Laitonjam, 2014;Rameshkumar et al 2015;Gao et al 2016) and also possess many pharmacological properties, such as; anti-inflammatory (Sikha et al 2015), antimicrobial (Jagtap, 2015), antirheumatic (Abdel-Lateef et al 2016), antiviral (Pant et al 2013), antifibrotic (Jose et al 2014) and antihepatotoxic (Jagtap, 2015); Antidiabetic (Nwozo et al 2014), anti-cancer (Pawar et al 2011) and also beneficial effects for cardiovascular disease (Nithya and Jayashree, 2017).…”
Section: Introductionmentioning
confidence: 99%